Some exact solutions of steady plane MHD non-Newtonian power-law fluid flows - Adluri, I. (Archives of Mechanics, 1999)
Equations of steady plane MHD flow of a non-Newtonian power-law fluid are transformed to the hodograph plane by means of the Legendre transform function of the stream-function. Results are summarized in the form of a theorem. As applications of the developed theory, four flow problems of physical interest are studied. Exact solutions and the corresponding geometry are obtained in each case.